DEVELOPMENT AND QUALITY EVALUATION OF BIODEGRADABLE EDIBLE CUTLERY: A REPLACEMENT FOR A CONVENTIONAL ONE - THAGUNNA, BISHAL; SHRESTHA, GRISHMA; KARKI, RACHANA; BARAL, KABUL; KAUR, JASPREET (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this research were to develop a safe, sustainable alternative to plastic cutlery using water, wheat flour, finger millet, rice flour, water, jaggery, oil, and salt in varying amounts. Methods: Edible cutlery was manufactured using a manual method by putting the dough on a steel spoon and cooking bowl and baking it at 180°C for 40 min and evaluating their proximate analysis, sensory attributes, water absorption capacity, and biodegradable test. Results: Sample S3 was found to be best in terms of nutrition including moisture, protein, fiber, fat, and ash (4.8, 7.23, 2.3, 3.7, and 1.97%). Carbohydrate content was found higher in S1 compared to S2 and S3 which are 90.43%. Similarly, S1 had the highest overall sensory attributes including color, appearance, texture, flavor, odor, and overall acceptability (7.64, 7.82, 6.91, 7.0, 6.9, and 7.45%) and has a high amount of water absorption capacity (31.59%) compared to S2 and S3. Conclusions: Biodegradable and edible cutlery would provide a completely new perspective and alternative to the fight against plastic pollution.